Aryl hydrocarbon receptor knock‐out exacerbates choroidal neovascularization via multiple pathogenic pathways. Issue 1 (10th October 2014) - Choudhary, Mayur; Kazmin, Dmitri; Hu, Peng; Thomas, Russell S; McDonnell, Donald P; Malek, Goldis
Abstract The aryl hydrocarbon receptor (AhR) is a heterodimeric transcriptional regulator with pleiotropic functions in xenobiotic metabolism and detoxification, vascular development and cancer. Herein, we report a previously undescribed role for the AhR signalling pathway in the pathogenesis of the wet, neovascular subtype of age‐related macular degeneration (AMD), the leading cause of vision loss in the elderly in the Western world. Comparative analysis of gene expression profiles of aged AhR−/− and wild‐type (wt) mice, using high‐throughput RNA sequencing, revealed differential modulation of genes belonging to several AMD‐related pathogenic pathways, including inflammation, angiogenesis and extracellular matrix regulation. To investigate AhR regulation of these pathways in wet AMD, we experimentally induced choroidal neovascular lesions in AhR−/− mice and found that they measured significantly larger in area and volume compared to age‐matched wt mice. Furthermore, these lesions displayed a higher number of ionized calcium‐binding adaptor molecule 1‐positive (Iba1+) microglial cells and a greater amount of collagen type IV deposition, events also seen in human wet AMD pathology specimens. Consistent with our in vivo observations, AhR knock‐down was sufficient to increase choroidal endothelial cell migration and tube formation in vitro. Moreover, AhR knock‐down caused an increase in collagen type IV production and secretion in both retinal pigment epithelial (RPE) and choroidal endothelial cell cultures, increased expression of angiogenic and inflammatory molecules, including vascular endothelial growth factor A (VEGFA) and chemokine (C–C motif) ligand 2 (CCL2) in RPE cells, and increased expression of secreted phosphoprotein 1 (SPP1) and transforming growth factor‐β1 (TGFβ1) in choroidal endothelial cells. Collectively, our findings identify AhR as a regulator of multiple pathogenic pathways in experimentally induced choroidal neovascularization, findings that are consistent with a possible role of AhR in wet AMD. The data discussed in this paper have been deposited in NCBI's Gene Expression Omnibus; GEO Submission No. GSE56983, NCBI Tracking System No. 17021116. © 2014 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.